PENGARUH SUSTAINABILITY REPORTING TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mulyani, Rani; Sumiyati, Sumiyati; Julia, Julia (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the effect of sustainability report disclosure on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX). The independent variables in this study include economic performance disclosure, environmental performance disclosure, and social performance disclosure. The dependent variable used is the stock price. The population of this study includes banking companies that disclose sustainability reports during the 2020-2023 period. The research sample consisted of 15 companies using purposive sampling technique and 4 years of observation. Data collection was carried out through the documentation method by analyzing the content of the sustainability report. The data analysis technique used is panel data regression. The results showed that partially the economic disclosure variable had a significant effect on stock prices while the social and environmental disclosure variables had no significant effect on stock prices. In addition, simultaneously, all independent variables have an influence on stock prices.